LONG-TERM VARIABILITY OF THE NOVA-LIKE VARIABLE V SGE - Marsakova, V. I.; Andronov, I. L.; Schweitzer, E. (Одеські астрономічні публікації, 2017)
V Sge was studied on photonegatives of the Moscow and Odessa plate collections. ln consequence of us analysis of these observations and of the AFOEV data, the two types of long-time variability were distinguished: (l) outbursts with characteristic time as ~212d ; (2) transitions between the high and low luminosity states with a cycle length ~250d; (3) variations with amplitude about 2m and smaller and at different time scales.